Aglomeração urbana descontínua: o exemplo de Araguari e Uberlândia/MG - Araújo, Flávia Aparecida Vieira de (2016)
The analysis of urban conurbations demands the understanding regarding the difference between urban territorial continuity and spatial continuity. While the spatial continuity is understood due to its interrelations and established fluxes, in other words, through the spatial integration, the territorial continuity is related to the urban tissue. Therefore, the spatial continuity can manifest in a simultaneous way or associated to the territorial discontinuity. From this perspective, the main objective of this research consists on identifying and dimensioning the spatial interactions that are driven to a urban conurbation process between the municipalities of Araguari and Uberlândia/MG, besides the not continuity of the territorial urban area. The intensity of these interactions was identified from the displacements by the dwellers from both municipalities in search of job occupations, education and health assistance. So it would be able to reach the proposed objectives we used several methodological procedures, such as a bibliographic and documental researches. In order to identify the education and work fluxes we analyzed the micro data from the Demographic Census 2010. For the educational sector it was also accomplished a research, in Araguari, the place of residence of students enrolled at Instituto Master de Ensino Presidente Antônio Carlos (IMEPAC) and, in Uberlândia, the place of residence of students enrolled at Universidade Federal de Uberlândia (UFU). The identification of health fluxes was done through a research, in Uberlândia, of the inpatients' origin at Hospital de Clínicas de Uberlândia of the Universidade Federal de Uberlândia (HCU/UFU) and, in Araguari, of the origin of patients that are attended at the Pronto-Socorro Municipal. Semi structured interviews were also accomplished with different social actors. Another important step was the use of questionnaires with the inter-municipal public transportation users at their boarding place in Araguari and Uberlândia. This paper was organized in five chapters, while in the first one we accomplished a theoretical discussion over the concept of urban conurbation, in order to presenting the identification and classification criteria and the urban conurbation of non metropolitan criteria. The second chapter analyses the differentiation process between Araguari and Uberlândia, which is a result of the distinct territorial formation of the municipalities. The third chapter analyses the intensity and degree of the spatial interactions between the two municipalities, having as a focus the established fluxes in the work sector. The fourth chapter, on the other hand, focuses on the education and health sectors, while the last chapter accomplishes a discussion to investigate if the analyzed fluxes in the previous chapters make it able to identify if the spatial interactions established between Araguari and Uberlândia are measured through complementarities or dependence. As a result it was possible to identify that, due to the expressiveness of the established fluxes between the two municipalities, beyond the further ones of Triângulo Mineiro and Alto Paranaíba in the three selected sectors, there is a configuration of a discontinuous urban conurbation process. It was also possible to conclude that, despite the fluxes between Araguari and Uberlândia being more representative than the other way around there's a coexistence dependence relationship and complementarity between the two municipalities.